Identity reconfiguration of immigrants in Portugal - Vieira, Ricardo (2010)
The starting point is the principle that there is no immigrant culture, but rather, different ways of living, coexisting and identifying oneself within the cultural worlds that each subject crosses on his or her social path. Here we study Brazilian immigrants in Portugal, working with the first wave (starting at the end of the 1980s) and the second wave (at the turn of the 20th to 21st century). We intend, firstly, to show how identity is reconstructed between two banks: the departure culture and the arrival culture. Secondly, we intend to give a voice to the most silent in the understanding of immigrants: the process of identity reconstruction of Brazilian immigrants is presented, resulting from ethno-biographic interviews. We will consider the cultural transfusion theory and observe the heterogeneous ways of living between cultures, whether by rejecting the departure culture (the Oblato’s case), refusing the arrival one at a given moment (the mono-cultural subject according to the source culture), living in an ambivalent manner between the two (the multicultural self), or, finally, inventing a third bank, as the poets say, which corresponds to an attitude of including the cultural differences through which one crosses during his or her life history in an intercultural self (the Intercultural Transfuga).